Research Methodology Design as a Foundation for the Development of Educational Science - Wildayah Musyafa; Muhammad Abdullah Sidiq; Vina Nanda Sugesti; Siti Khotimah; Idham Kholid; Bambang Sri Anggoro; Mujib Mujib; Mardiyah Mardiyah (al-Afkar, Journal For Islamic Studies, 2026)
Research methodology is crucial for the advancement of educational science. For research to be conducted systematically and purposefully, an appropriate methodological design is necessary. The purpose of this article is to explore ideas about research methodology design and its role as a foundation for the advancement of educational science. This study employed a qualitative methodology, along with a library research approach. Data were obtained from various sources, such as research methodology books, scientific journals, and educational research articles. In the documentation, various references related to research methodology were reviewed to facilitate the data collection process. The results of the study indicate that research methodology design encompasses many concepts and theories related to the research problem. The study demonstrates that research methodology design encompasses the formulation of the research problem, the selected research method, data collection techniques, data analysis techniques, and systematic research procedures. An effective research methodology design will assist researchers.